2006
DOI: 10.1007/s10531-004-1870-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Disturbances and Diversity Increase: Implications for Invertebrate Conservation

Abstract: The Pantanal is one of the faunistic provinces considered as a priority area for invertebrate conservation. However, it is one of the areas in Brazil where the local fauna is less assessed, thus needing more scientific information that could allow political decisions to be made regarding conservation. The continuous pressure for new pasture areas leads to improper habitat occupation and destruction, like fragmentation of forest areas in the region. Such alterations can cause different impacts on the local faun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…This provides some of the first evidence that non-consumptive effects of predators can reach beyond individual species (e.g., Fill et al 2012;Hill and Weissburg 2013) to influence entire food webs. Our findings are also consistent with the literature pointing to the considerable susceptibility of soil and litter invertebrates to abiotic and biotic soil physical disturbance, especially the disturbance associated with cultivation (Hendrix et al 1986;Wardle 2002;Loyola et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…This provides some of the first evidence that non-consumptive effects of predators can reach beyond individual species (e.g., Fill et al 2012;Hill and Weissburg 2013) to influence entire food webs. Our findings are also consistent with the literature pointing to the considerable susceptibility of soil and litter invertebrates to abiotic and biotic soil physical disturbance, especially the disturbance associated with cultivation (Hendrix et al 1986;Wardle 2002;Loyola et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Loyola et al (2006) found this same pattern when studying the invertebrate community in areas of forest and pasture in Pantanal wetlands, while Ferreira and Marques (1998) verified low similarity between litter arthropod communities of secondary forest and Eucalyptus monoculture, as well as, arthropod richness and diversity of secondary forest and Eucalyptus monoculture. All these results, therefore, corroborate with the evidences, that modifications of natural ecosystems caused by human activities generate changes in composition and structure of biological communities (Hillebrand et al, 2008).…”
Section: Resultsmentioning
confidence: 73%
“…For the cavity‐nesting species, the nest‐trap methodology is widely used for their monitoring since it allows to survey only the species that occur in the studied region, excluding those that are just transiting (Assis & Camillo 1997; Araújo et al 2018b; Araújo et al 2019). In natural environments, the community composition of bees and wasps is closely correlated with availability of food, nesting sites, and favorable microclimatic conditions (Loyola & Brito 2006; Tylianakis et al 2006; Araújo et al 2018b). Temporal variation in resources and environmental conditions over time is frequently reflected in variation in species composition (Matos et al 2016), acting as environmental filters that influence the colonization or persistence of healthy populations in disturbed habitats (Loyola & Martins 2006; Antonini et al 2016; Matos et al 2016; Araújo et al 2019).…”
Section: Introductionmentioning
confidence: 99%